Digital Transformation in Supply Chain Management to Enhance Efficiency, Transparency, and Business Sustainability in the Global Era - Gucchi, Anjaka Ray (Jurnal Ar Ro'is Mandalika (Armada), 2025)
In today’s globalized marketplace, supply chains are under immense pressure to operate with greater efficiency, transparency, and sustainability. Rapid technological advancements—such as blockchain, artificial intelligence (AI), the Internet of Things (IoT), and advanced analytics—are enabling firms to reconfigure traditional processes and achieve these goals simultaneously. This study aims to develop an integrated framework of digital transformation in supply chain management, focusing on its impact on efficiency, transparency, and business sustainability. Using a qualitative literature review method, data were drawn from recent scholarly articles, industry reports, and institutional publications to provide a comprehensive understanding of digital transformation practices. Findings indicate that blockchain enhances trust and transparency through immutable records; IoT improves efficiency via real-time monitoring and predictive maintenance; and AI, when combined with big data, enables proactive decision-making and resource optimization. Importantly, these technologies achieve maximum impact when embedded within redesigned business processes and compliance mechanisms, ensuring alignment with environmental, social, and governance (ESG) standards. The study also highlights significant sustainability outcomes, including waste reduction, carbon footprint minimization, and ethical sourcing verification, with real-world applications observed in industries such as food, logistics, and manufacturing. Overall, this research contributes to both theory and practice by presenting a holistic digital transformation model that integrates technological enablers, process redesign, and compliance systems. This framework provides managers with actionable guidance to align digital adoption with strategic objectives, regulatory demands, and long-term sustainability imperatives.